Professor Paavo Komi nordic skiing memorial - Linnamo, V. (Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing, 2020)
Professor Paavo V. Komi (1939-2018) dedicated his Professional life to studying human movement and developing novel methodologies to understand the mechanisms behind different phenomena. For example, the buckle transducer and optic fiber techniques, as well as the sledge apparatus to examine the Stretch shortening cycle, became known to the scientific community all over the world. He received seven honorary doctorates and numerous international and national prestigious awards, and served as President in organizations such as the International Society of Biomechanics (ISB), World Commission of Sports Biomechanics, International Council of Sport Science and Physical Education (ICSSPE), and European College of Sport Science (ECSS).